Evaluation of Anticancer Potential of Humic Acid and Fulvic Acid Against Breast Carcinoma - Tapasree Basu; Anil Khushalrao Shendge; Nripendranath Mandal (International Journal of Pharma and Bio Sciences, 2021)
Breast cancer is the primary cancer affecting women worldwide. Humic and fulvic acids being phenolic polymers are known for anti-inflammatory, anti-neoplastic, analgesic and anti-microbial properties. However, their role in carcinogenesis is unclear. In search of new anticancer drugs, we have extracted humic (HAF) and fulvic acids (FAF) rich fractions from dried cow dung and used for further study. HAF and FAF were characterized using FTIR analysis. We performed antioxidant and cytotoxicity assays, flow cytometry, confocal microscopy, western blotting and statistical analyses to substantiate HAF and FAF as potential antioxidant and anticancer drug candidates. It was observed that HAF and FAF were potent free radical scavengers and promising antioxidants in vitro. Both HAF and FAF triggers apoptotic cell death through selective loss of MCF-7 cell viability, morphological changes, chromosomal condensation and sub-G1 accumulation. Western blot analysis revealed the molecular markers of apoptosis associated with extrinsic and intrinsic pathways indicating ‘cytochrome C’ release from mitochondria, cleavage of pro-caspases 8, 9 and 3 followed by Bid truncation, native PARP degradation and dysregulation of Bax/Bcl-2 ratio. Further investigations showed that HAF and FAF selectively induced intracellular ROS in MCF-7 cells and suppressed the activation of ERK1/2, upregulated JNK, p38 mitogen-activated protein kinase pathways in malignant cells. Moreover p53 is upregulated in both the treatments. In this investigation, it has been reported that there is involvement of apoptotic proteins, p53 and MAP kinases which establishes the antioxidant and anti-cancer nature of HAF and FAF against MCF-7 cells. The present study will be helpful for the scientific community to develop better anticancer drug against breast carcinoma. Nevertheless, specific lead compound isolation and further in-depth study is required for development of anticancer drug.